PENGARUH RELATIONSHIP MARKETING DAN LAYANAN PURNA JUAL TERHADAP KEPUSAN KONSUMEN MOBIL MEREK NISSAN PadaKonsumen Dealer Nissan PT. WahanaWirawanPekanbaru - Janromeiya Saragih; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the influence of relationship marketing and after sales service to the consumer car brand kepusan Nissan Consumer Nissan Dealer PT. Wahana Wirawan Pekanbaru, where proposed two independent variables and one dependent variable, namely relationship marketing and after-sales service as an independent variable and customer satisfaction acts as a dependent variable.This research method is descriptive and quantitative by using SPSS 21 program, where the sample used is consumer of Nissan Dealer PT. Wahana Wirawan Pekanbaru with 100 respondents. For sampling technique using snowball method. Technique of collecting data through kusioner and interview.The results of analysis using the validity test, reliability test, detemination test, simple linear ujiregresi, multiple linear expressions, t test, and f test so that it can be seen that Relationship Marketing has a significant effect on customer satisfaction, that after sales service significantly influence consumer satisfaction, Relationship marketing and post-sale services have a significant effect on customer satisfaction.Keywords: Relationship Marketing, After Sales Service and Consumer Satisfaction